FROM THE HISTORY OF THE INTRODUCTION OF THE EDUCATION SYSTEM FOR THE NEEDS OF THE INDIGENOUS POPULATION OF THE TRANSCASPIAN REGION (LATE XIX - EARLY XIX CENTURIES) - Khaynazarov Bahromjon, (Social science and innovation, 2023)
The article analyzes such issues as changes in the education system after the conquest of the Turkestan region by the Russian Empire, in particular, the opening of new schools in the Caspian region in the Governor-General of Turkestan, the process of training teachers for new schools, attempts to train personnel suitable for socio-economic changes, public participation